2019
DOI: 10.3390/w11122578
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Reveals Tap Water Source under Different Water Supply Modes in the Eastern Margin of the Qinghai–Tibet Plateau

Abstract: Based on 1260 tap water samples gathered monthly and 136 surface water samples collected seasonally in the eastern margin of the Qinghai–Tibet Plateau, the local tap water line, the basic spatiotemporal characteristics of tap water isotopes, and their indication for water source under different water supply modes were discussed, linking the local tap water supply and water source information. A new tap water isotopes data set based on dense sampling sites was established, which was reliable for the analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…In the Qinghai-Tibet Plateau (China), Du et al [28] found that the stable isotope values of tap water could indicate particular sources in the case of a mixed water supply. The stable isotope values of tap water showed spatial patterns across the region and indicated a dominant surface water signal.…”
Section: Similar Studies In Ukraine and Worldwidementioning
confidence: 99%
“…In the Qinghai-Tibet Plateau (China), Du et al [28] found that the stable isotope values of tap water could indicate particular sources in the case of a mixed water supply. The stable isotope values of tap water showed spatial patterns across the region and indicated a dominant surface water signal.…”
Section: Similar Studies In Ukraine and Worldwidementioning
confidence: 99%